Evaluating ICT literacy: Physics ICT test based on Scratch Programming for high school students - Rusilowati, Ani; Negoro, Ridho Adi; Subali, Bambang; Aji, Mahardika Prasetya (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
The integration of various learning content is important in the education process to develop the multi-competences of graduates. This is a response to the Industrial Revolution 4.0. ICT helps graduates compete and master the competencies needed in various scientific fields, especially physics. Efforts to build ICT literacy in learning Physics must complete an evaluation tool containing comprehensive Physics content. The ICT literacy test instrument as an evaluation tool can be packaged with scratch programming activities to help uncover ICT literacy based on computational physics concepts. This study aims to develop an ICT literacy test instrument with physics content based on Scratch programming for middle-level students. This research is development research with a research stage adapted from the development stage by Borg and Gall, including (1) Potential and problem analysis; (2) Data collection; (3) Product design; (4) Design validation and design revision; (5) Product trial; (6) Analysis and reporting. The test subjects were 106 students. The Physics ICT questions were developed to consist of 20 questions. Based on the validity test, a total percentage of 85.33% is obtained with proper criteria. The reliability of the test is shown by the results of calculations with Alpha Cron of 0.716 high categories. Overall, the PICT test is feasible to be used as an ICT literacy test for Physics content.